Noncovalent Se···O Conformational Locks for Constructing High‐Performing Optoelectronic Conjugated Polymers. Issue 34 (10th July 2017) - Dong, Tao; Lv, Lei; Feng, Linlin; Xia, Yu; Deng, Wei; Ye, Pan; Yang, Bei; Ding, Shang; Facchetti, Antonio; Dong, Huanli; Huang, Hui
Abstract : Noncovalent conformational locks are broadly employed to construct highly planar π‐conjugated semiconductors exhibiting substantial charge transport characteristics. However, current chalcogen‐based conformational lock strategies for organic semiconductors are limited to S···X (X = O, N, halide) weak interactions. An easily accessible (minimal synthetic steps) and structurally planar selenophene‐based building block, 1, 2‐diethoxy‐1, 2‐bisselenylvinylene (DESVS ), with novel Se···O noncovalent conformational locks is designed and synthesized.DESVS unique properties are supported by density functional theory computed electronic structures, single crystal structures, and experimental lattice cohesion metrics. Based on this building block, a new class of stable, structurally planar, and solution‐processable conjugated polymers are synthesized and implemented in organic thin‐film transistors (TFT) and organic photovoltaic (OPV) cells.DESVS ‐based polymers exhibit carrier mobilities in air as high as 1.49 cm 2 V −1 s −1 (p‐type) and 0.65 cm 2 V −1 s −1 (n‐type) in TFTs, and power conversion efficiency >5% in OPV cells. Abstract : Noncovalent "Se···O" conformational locks for high‐performance conjugated polymers : an easily accessible and structurally planar selenophene‐based building block with novel Se···O noncovalent conformational locks is designed and synthesized, which affords polymer thin‐film transistors with charge‐carrier mobilities in air as high as 1.49 cm 2 V −1 s −1 (p‐type) and 0.65 cm 2 V −1 s −1 (n‐type), and organic photovoltaic cells with power conversion efficiency >5%.